Pursuing the developmental aims of the triarchic model of psychopathy: Creation and validation of triarchic scales for use in the USC: RFAB longitudinal twin project. (15th August 2022) - Bertoldi, Bridget M.; Perkins, Emily R.; Tuvblad, Catherine; Oskarsson, Sofi; Kramer, Mark D.; Latzman, Robert D.; Baker, Laura A.; Raine, Adrian; Patrick, Christopher J.
Abstract: The triarchic model was advanced as an integrative, trait-based framework for investigating psychopathy using different assessment methods and across developmental periods. Recent research has shown that the triarchic traits of boldness, meanness, and disinhibition can be operationalized effectively in youth, but longitudinal research is needed to realize the model's potential to advance developmental understanding of psychopathy. We report on the creation and validation of scale measures of the triarchic traits using questionnaire items available in the University of Southern California Risk Factors for Antisocial Behavior (RFAB) project, a large-scale longitudinal study of the development of antisocial behavior that includes measures from multiple modalities (self-report, informant rating, clinical-diagnostic, task-behavioral, physiological). Using a construct-rating and psychometric refinement approach, we developed triarchic scales that showed acceptable reliability, expected intercorrelations, and good temporal stability. The scales showed theory-consistent relations with external criteria including measures of psychopathy, internalizing/externalizing psychopathology, antisocial behavior, and substance use. Findings demonstrate the viability of measuring triarchic traits in the RFAB sample, extend the known nomological network of these traits into the developmental realm, and provide a foundation for follow-up studies examining the etiology of psychopathic traits and their relations with multimodal measures of cognitive-affective function and proneness to clinical problems.